The nonobserved economy in the European Union - Óscar Afonso (2017)
To better understand the share of the nonobserved economy (NOE) in the European Union, especially on the PIIGS, we estimate, through the multiple indicators multiple causes model, the path between 1980 and 2013. The model includes (i) the tax burden (disaggregated into direct and indirect taxes), a proxy of regulation burden, the unemployment rate and self-employment as causes of the NOE economy; (ii) the GDP and the labour force participation ratio as indicators of the NOE economy. In particular, the estimated weight of NOE as a percentage of official GDP was always higher in the PIIGS group.